HUBUNGAN FAKTOR PENDORONG DAN PENDUKUNG PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SUKARAMAI KABUPATEN PAKPAK BHARAT - Tinendung, Dewi Srirahayu; Okrianti, Surisna (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Breastfeeding exclusively is very important for the health and endurance babies because breast milk contains nutrients height needed for the growth and development of nerve and brain. Scope of exclusive breastfeeding in Indonesia in general is still low at 54.3% of the 80% target, as well as health centers in the region of Sukaramai only 45.3%. This research is analytic survey with cross sectional design study aimed to analyze the relationship between predisposing factors (knowledge, attitudes, traditions and beliefs), support (advertising formula), plunger (family support, support health workers) against exclusive breastfeeding in the region Sukaramai health centers. the population in this study were all mothers of infants aged 6-12 months size of 208 mother in the region Sukaramai health centers, with a sample size of 112 mother. The data collection includes data referring to the kueisoner primary and secondary data from health center records Sukaramai. Data analysis using chi square test and multiple logistic regression on the level of 95%. The results showed 34.8% of mothers gave exclusive breastfeeding in the working area Sukaramai health centers. Chi square test results showed that variables associated with exclusive breastfeeding in the work area Sukaramai health centers are knowledge (p = 0.003), traditions and beliefs (p = 0.0001) and family support (p= 0.0001). The results of logistic regression showed that variables traditions and beliefs (p = 0.0001) were significantly related to exclusive breastfeeding in mothers in the working area Sukaramai health centers. It is suggested to members of the family, especially to her husband in order to motivate and support mothers breastfeed exclusion, and to the health centers need to increase socialization and counseling on exclusive breastfeeding routine.Keywords: Enabling Factors, Reinforcing Factors, Exclusive breastfeeding